Analisis Program Peningkatan Ketahanan Pangan Rumahtangga Petani Ikan Nila Di Kecamatan Pringgarata - Suparmin Suparmin; Bambang Dipokusumo (Universitas Mataram, 2022)
This study aims to: 1) analyze the income sources of tilapia famer’s household , 2) describe the income distribution pattern of farmers' households, 3) describe the distribution pattern of farmer household expenditures, and 4) analyze the level of food security of farmer households. This research uses a descriptive method. Research with descriptive method designed in the form of survey research. Data was collected using triangulation techniques, namely by combining three research techniques together, namely: (1) interview techniques (interviews) with respondents; (2) field observations (field observations); and (3) literature study (desk study). The research area is Pringgarata District, Central Lombok Regency. From the 11 villages, a village was chosen, namely Pringgarata village. Furthermore, data collection on farmer households was carried out. The farmer households that became the research sample were selected by random sampling as many as 15 farmer households. Farmer households here are farmer households who have jobs as tilapia fish cultivators. The results of the study concluded that first, the sources of household income for tilapia fish cultivators in Pringgarata village varied. Likewise, the household expenditure of farmers also varies. Second, the distribution pattern of farmers' household income is sourced from tilapia cultivation and outside tilapia cultivation. Activities outside of tilapia cultivation such as farming (rice, secondary crops, vegetables), trading, workshops, labor. The average household income of farmers for one season or 6 months is IDR 28,548,000, -,. Third, the distribution pattern of farmer household expenditures in Pringgarata village is divided into food and non-food expenditures. The average household expenditure of farmers during one season is IDR 7,610,600, for food is IDR 3,683,100, and for non-food is IDR 7,610,600, - and fourth, household food security of tilapia fish cultivators in Pringgarata village. belong to food-secure households.